Does legal capacity matter for inclusive economic development? Empirical evidence from Southern Africa - George Banda, Lloyd (Ius Humani. Jornal do direito, 2024)
The legal capacity or, otherwise, the institutions of rule of law (RL), have become a key factor for inclusive economic development, but the main strands of the literature involve theoretically driven expectations. Therefore, the study sought to examine the impact of legal capacity on inclusive economic development in the Southern African Development Community (SADC) region. While extant studies focused on the effect of governance on national output, the present study goes beyond growth by including welfare indicators. The study employed a panel autoregressive distributed lag (ARDL) approach for data from all 16 SADC member states from 1996 to 2019. The interpretation of results and policy implications are based on the outcomes of the pooled mean group (PMG) estimator, which was deemed by the Hausman test as the best and most efficient estimator over the MG and the DFE family of the ARDL panel estimators. The results of the restricted panel reveal that strengthening the institutions of the RL leads to an improvement in inclusive economic development among SADC states. Therefore, we argue that trade laws should be domestically integrated and embedded in SADC's national laws, and that common courts should be set to adjudicate disagreements over compliance. We also propose that SADC introduce incentives to increase legal stakeholders' participation across the region.